Euboean towers and Aegean powers: insights into the Karystia’s role in the ancient world - Gardner, Chelsea A. M.; Seifried, Rebecca M. (Journal of Greek Archaeology, 2016)
The Karystia, a region of southern Euboea directly across from the Attic mainland, features two peninsulas that are dry and agriculturally poor compared to the fertile plains found elsewhere in the region and on the island (Figure 1). Despite the aridity of this area, however, an unusual pattern of human activity was revealed during archaeological investigation and extensive survey carried out in the 1980s and the 1990s. The Paximadi peninsula was first explored by Donald Keller during his dissertation research between 1979–1981, and between 1986–1993 the Southern Euboea Exploration Project (SEEP) continued work on both the Paximadi and the Bouros-Kastri peninsulas. These surveys recorded a dispersed settlement pattern of single farmsteads, along with an exceptionally high number of tower structures on the two peninsulas that flank ancient Karystos—a site now identified with the modern town of Paliochora (Figure 2). The majority of the towers date to the Classical period, though others range from the Archaic through Ottoman periods. At present, only the towers of Paximadi have been published, so their connections with those of Bouros-Kastri and with the broader Aegean have yet to be fully elucidated. This paper reviews different explanations for the unusually high density of Classical-period towers in this region, contextualizes the towers within the period of classical antiquity to which they are most likely to belong (the 5th century BC), and presents a new interpretation of nearly three-decade-old data that underscores the importance of the Karystia in the ancient Aegean.